HIDDEN SEQUENCES IN RESULTS OF TESTS IDENTIFYING - Yutskevych, Sviatoslav (Proceedings of National Aviation University, 2013)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><span style="font-size: 10.0pt; font-family: "Times New Roman"; mso-fareast-font-family: "MS Mincho"; mso-ansi-language: UK; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold;" lang="UK">Describes a method and a general algorithm for the experimental data series corresponding to a given recurrence relation search program. Search-analytical model different from the existing search models is offered<!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>